Digital-Chaos Ventures : Rise n go smart pillow / Muhammad Afif Fiqri Bin Zulkafli ...[et al.] - Zulkafli, Muhammad Afif Fiqri; Mustam, Nursyafiq Haziq; Mohd Raduan, Muhammad Ibad Haziq; Tajuddin, Nur Syazwani (2019)
Rise N Go Smart Pillow is a developing business that motivated to help people to have a comfortable and good quality of nap and sleep everyday. The slogan of the Rise N go Smart Pillow is “ Good Sleep Good life” , Which emphasizes that to have a healthy lifestyle a person need to have a good sleep. It was inspired through an experience when someone face difficulty to sleep early and wake up early in the morning. This problems lead them to another greater problems such as coming late to works and school. Rise N Go smart Pillow maximizes comfort by capitalizing on the everyday functions of the consumer. Everyone has the need of being comfortable and Rise N Go Smart Pillow mission is to meet the need. Rise N go Smart Pillow has created a simple design that was develop from a regular pillow. The Rise N Go Smart pillow consist of massaging components the will help consumer to have a good and relaxing time. Other than that, the pillow will be having an alarm to help consumer to wake up easily in the morning. The pillow can be used by all age of consumers because it is safe and comfortable. The pillow will be distributed to the residential, school and furniture area because the main target is the customers that lives in a home.